FAKTOR FUNDAMENTAL YANG MEMPENGARUHI BETA SAHAM PERUSAHAAN INDUSTRI DI BURSA EFEK INDONESIA - Koko Denik Wahyudi; Siti Husnul Hotima (Majalah Ilmiah DIAN ILMU, 2014)
This research is how to measure the influences of the Current Ratio, Asset Growth, Total Assets Turn Over, Firm Size, and Financial Laverage against Beta Stock (sistematic risk  of stock) either simultaneously or partially. This research is  done on 16th Automotive Indurstrial Companies which are registered in Indonesian Stock Exchange during periode in 2004 to 2012. The analisis which is used in this research is the multiple linier regression alayisis with model   BS=b0+b1CR+b2AG+b3FS+b4ATO b5FL+e. Analysis results: (1) Current Ratio (CR), Asset Growth (AG), Total Assets Turn Over (ATO), Firm Size (FZ), and Financial Laverage(LR)  influence simultaneously against Beta Stock in significant way. (2) Current Ratio, Asset Growth, Total Assets Turn Over, Firm Size, and Financial Laverage influence partially against Beta Stock in significant way. (3) The Strongest influence against beta stock (sistematic risk of Stock) is Total Assets Turn Over.